PENGARUH RASIO LIKUIDITAS, RASIO SOLVABILITAS DAN RASIO MANAJEMEN AKTIVA TERHADAP PERTUMBUHAN LABA PADA SEKTOR PROPERTI, REAL ESTATE, DAN KONSTRUKSI BANGUNAN - Chatarine (Fakultas Ekonomi dan Bisnis Universitas Bung Hatta, 2023)
The purpose of this study is to determine the impcat of the debt to equity ratio, total asset turnover and current ratio on profit growth in the property, real estate and building construction sectors listed on the IDX for the 2016-2019 period. The data used in this study is secondary data obtained from financial reports and downloaded through the IDX's official website, www.idx.co.id. The study uses a purposive sampling technique. is The multiple linear regression analysis used to test the hypothesis. The results of this study indicate that the variables Debt to Equity Ratio, Total Asset Turnover, and Current Ratio simultaneously and partially have no impact on Profit Growth.